Adaptive management of fisheries in response to climate change - Bahri, T., Vasconcellos, M., Welch, D.J., Johnson, J., Perry, R.I., Ma, X.; Sharma, R., eds. (My University, 2021)
The yellow clam (Mesodesma mactroides) is a cool-water species that is harvested by artisanal fishers along warm-temperate sandy beaches of the Atlantic coast of South America. This region represents a major global-warming hotspot, where sea surface temperature has been dramatically increasing since the mid-1990s, when a shift in the ocean&ndashclimate regime from a cold to a warm period was detected. Yellow clam populations suffered mass mortalities that followed the poleward shift of the warm water front. A long-term decrease in abundance and individual size, as well as increasing signs of deteriorating body condition, have also been documented. In Uruguay the fishery was reopened 14 years after mass mortalities, when the resource showed signs of recovery, even though abundance never reached pre-mortality levels. A precautionary management approach included a conservative catch quota allocated equally to a reduced number of local fishers. The institutionalization of co-management was a key factor in coping with variations in climate, strengthening collaboration among stakeholders and providing rules and action mechanisms in the face of climate-driven stressors. A shift in the marketing strategy allowed fishers to maximize economic benefits. Currently, unfavourable weather events and an increase in intensity and frequency of harmful algal blooms restrict the number of fishable days. Weekly phytoplankton and toxin monitoring is being carried out as an adaptive management measure to cope with this stressor and to safeguard seafood health and safety. Imported seafood on local markets also exacerbates the situation by providing an alternative and competing source of clams. Flexible policies and management actions are needed to tackle the challenge of promoting a climate-resilient and adaptable small-scale local fishery.
Keywords: adaptive management; fisheries; climate change